An Introduction to Soil Dynamics - Verruijt, Arnold. (Theory and Applications of Transport in Porous Media,, 2010)
This book presents the basic principles of soil dynamics, and a variety of solutions of practical interest for geotechnical engineering, geophysics and earthquake engineering. Emphasis is on analytical solutions, often including the full derivation of the solution, and giving the main parts of computer programs that can be used to calculate numerical data. Reference is also made to a website from which complete computer programs can be downloaded. Soil behaviour is usually assumed to be linear elastic, but in many cases the effect of viscous damping or hysteretic damping, due to plastic deformations, is also considered. Special features are: the analysis of wave propagation in saturated compressible porous media, approximate analysis of the generation of Rayleigh waves, the analysis of the response of soil layers to earthquakes in the deep rock, with a theoretical foundation of such problems by the propagation of Love waves, and the solution of such basic problems as the response of an elastic half space to point loads, line loads, strip loads and moving loads. - Includes detailed derivations of solutions - Includes listings of main parts of computer programs - Computer programs are available from the website http://geo.verruijt.net - Includes dynamics of porous media Audience: Students and staff in soil dynamics at civil engineering, geophysics and earthquake engineering departments. .